A Survey of the Impact of Patient Adverse Events and near Misses on Anaesthetists in Australia and New Zealand. Issue 5 (September 2018) - Harrison, R.; Lee, H.; Sharma, A.
We conducted a cross-sectional online survey of members of the Australian and New Zealand College of Anaesthetists to investigate their experiences of adverse patient safety events and near misses, including their use of incident reporting systems and the organisational support available. There were 247 respondents. Of the 243 anaesthetists whose patients had an adverse event or near miss, 199 reported this had affected them personally or professionally; 177 reported stress, 153 anxiety, 109 sleep disturbance, and 127 lower professional confidence. Of 188 who had reported an adverse event using their local incident reporting systems, 68 were satisfied with this process, 136 received useful feedback, 114 saw local improvements, and 104 saw system changes. Two hundred and thirty-four reported feeling determined to improve, and 228 were anxious about the potential for future errors. Seventy-five anaesthetists admitted not reporting a safety incident that they knew they should have. Reasons for not reporting included an impression that nothing would improve from incident reporting, that reporting was onerous, or fears of punitive action. These findings should spur anaesthetists, anaesthetic departments and professional organisations across Australia and New Zealand to examine their support mechanisms in relation to adverse events and errors and their incident reporting mechanisms, and to attempt to improve these services where necessary.